Is sickle cell disease a risk factor for severe COVID‐19 outcomes in hospitalized patients? A multicenter national retrospective cohort study. Issue 2 (10th February 2021) - Abdulrahman, Abdulkarim; Wael, Mohammed; AlAmmadi, Fajer; Almosawi, Zahra; Alsherooqi, Reem; Abduljalil, Manal; Kumar, Nitya; AlQahtani, Manaf
Abstract: Introduction: Studies that examine the association between sickle cell disease (SCD) and COVID‐19 outcomes are lacking. This study aims to determine whether SCD is a risk factor for severe COVID‐19 infection in regard to the requirement of noninvasive ventilation/high flow nasal cannula (NIV/HFNC), mechanical ventilation (MV), or death in hospitalized patients. Methods: Retrospective cohort study included COVID‐19 patients admitted to four COVID‐19 treatment facilities in Bahrain between February 24, 2020 and July 31, 2020. All SCD patients with COVID‐19 were included and compared to a randomly selected sample of non‐SCD patients with COVID‐19. Data were collected from the medical records. Multivariate logistic regression models were used to control for confounders and estimate the effect of SCD on the outcomes. Results: 1792 patients with COVID‐19 were included; 38 of whom were diagnosed with SCD as well. In the SCD group, one (2.6%) patient required NIV/HFNC, one (2.6%) required MV, and one (2.6%) death occurred. In comparison, 56 (3.2%) of the non‐SCD patients required NIV/HFNC, 47 (2.7%) required MV, and death occurred in 58 (3.3%) patients. Upon adjusting for confounders, SCD had an odds ratio of 1.847 (95% CI: 0.39–8.83; p = 0.442). Conclusion: Our results indicate that SCD is not a risk factor for worse COVID‐19 outcomes in hospitalized patients.